Variation in CD8 T cell IFNγ differentiation to strains of Toxoplasma gondii is characterized by small effect QTLs with contribution from ROP16 - Kongsomboonvech, Angel K.; García-López, Laura; Njume, Ferdinand; Rodriguez, Felipe; Souza, Scott P.; Rosenberg, Alex; Jensen, Kirk D. C. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Toxoplasma gondii induces a strong CD8 T cell response characterized by the secretion of IFNγ that promotes host survival during infection. The initiation of CD8 T cell IFNγ responses in vitro differs widely between clonal lineage strains of T. gondii, in which type I strains are low inducers, while types II and III strains are high inducers. We hypothesized this phenotype is due to a polymorphic “Regulator Of CD8 T cell Response” (ROCTR). Methods Therefore, we screened F1 progeny from genetic crosses between the clonal lineage strains to identify ROCTR. Naïve antigen-specific CD8 T cells (T57) isolated from transnuclear mice, which are specific for the endogenous and vacuolar TGD057 antigen, were measured for their ability to become activated, transcribe Ifng and produce IFNγ in response to T. gondii infected macrophages. Results Genetic mapping returned four non-interacting quantitative trait loci (QTL) with small effect on T. gondii chromosomes (chr) VIIb-VIII, X and XII. These loci encompass multiple gene candidates highlighted by ROP16 (chrVIIb-VIII), GRA35 (chrX), TgNSM (chrX), and a pair of uncharacterized NTPases (chrXII), whose locus we report to be significantly truncated in the type I RH background. Although none of the chromosome X and XII candidates bore evidence for regulating CD8 T cell IFNγ responses, type I variants of ROP16 lowered Ifng transcription early after T cell activation. During our search for ROCTR, we also noted the parasitophorous vacuole membrane (PVM) targeting factor for dense granules (GRAs), GRA43, repressed the response suggesting PVM-associated GRAs are important for CD8 T cell activation. Furthermore, RIPK3 expression in macrophages was an absolute requirement for CD8 T cell IFNγ differentiation implicating the necroptosis pathway in T cell immunity to T. gondii. Discussion Collectively, our data suggest that while CD8 T cell IFNγ production to T. gondii strains vary dramatically, it is not controlled by a single polymorphism with strong effect. However, early in the differentiation process, polymorphisms in ROP16 can regulate commitment of responding CD8 T cells to IFNγ production which may have bearing on immunity to T. gondii.